Pengaruh Online Review Promo Diskon Dan Kepercayaan Terhadap Keputusan Pembelan Pada E-Commerce Tiktokshop - Widyanti Kusuma Wardani; Nurhidayah Nurhidayah; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of online reviews, discount promos and trust on purchasing decisions. The research used is a quantitative method. The population in this study were students of the Faculty of Economics and Business, Islamic University of Malang. While the sample used in this study is Non-Probability Sampling using the Maholtra formula so there are 75 samples. The data used is primary data by using a questionnaire. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the partial results of the study, it was found that online reviews had a significant effect on purchasing decisions, discount promos had no effect on purchasing decisions, and trust had an effect on purchasing decisions. Keyword : Online review, discount promos, trust and buying decision.